The Charcoal Quantification Tool (CharTool): A Suite of Open-source Tools for Quantifying Charcoal Fragments and Sediment Properties in Archaeological and Paleoecological Analysis - Snitker, Grant (Ethnobiology Letters, 2020)
Sedimentary charcoal analysis is increasingly used in archaeological and paleoecological research to examine human-environmental relationships at multiple scales. The recent availability of low-cost digital microscopes and imaging software has resulted in the rapid adoption of digital image analysis in charcoal studies. However, most published studies include only minimal accounts of software configurations or utilize proprietary image analysis programs, thus hindering replication, standardization, and comparability of charcoal analyses across the field. In an effort to encourage replicable methods and a culture of open science, this paper presents the Charcoal Quantification Tool (CharTool), a free, open-source suite of charcoal and sediment quantification tools designed for use with ImageJ. CharTool blends standard methods in visual and digital charcoal analysis to increase the analyst’s participation in identifying and measuring charcoal metrics. Each CharTool module is described and demonstrated in a vignette using sedimentary charcoal collected from the Son Servera study area, Mallorca, Spain. A suggested workflow, user-guide, scripted analyses for processing outputs, and download instructions are included as supplementary materials to this article.